VISUALIZING INFLUENCE, AMPLIFYING LEARNING: A PRE-POST STUDY OF ONLINE INFLUENCER MAPPING - Annuar, Sharifah Nurafizah Syed (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Influencer mapping is a fundamental skill in marketing education, allowing the students to be able to recognize and examine key stakeholders. Nevertheless, existing literature lacks discussions and empirical evidence on the effectiveness of online mapping methods particularly in influencer mapping in enhancing student learning. Thus, the objective of this paper is to address the gap by investigating the effects of online influencer mapping on student learning within a marketing education context. This study employs qualitative study by assessing pre and post-test open ended survey. 15 students participated in an influencer mapping task using digital platform where they are required to create and refine influencers map. The pre and post study were designed to evaluate their learning gain, skill development, self-efficacy and attitude. Thematic and descriptive analysis were conducted and the analysis discovered substantial increases in student understanding, mapping abilities, and confidence in stakeholder analysis. The findings emphasize the capability of online tools to improve experiential learning, suggesting practical understandings for educators in digital settings.